Transference Number Measurement of Zinc Salts in Aqueous Solution (Baghdad Science Journal, 2025)
Transference numbers of the aqueous zinc chloride and zinc sulphate solutions have been measured for the concentrations 0.03, 0.05, 0.07, 0.09 and 0.1 mol.dm-3at 298.15K, by using the modified Hittorf method. The dependence of transference number on concentration of each electrolyte was also investigated in an attempt to explain the value of the limiting transference number. The Longsworth method has been used for the extrapolation of zinc transference number in aqueous solutions, using the values of the limiting transference numbers of the appropriate values of the limiting equivalent conductance, it was possible to determine the corresponding values of the limiting ion conductance for the cations and anions of the electrolytes. The density and specific conductivity of all solutions have been measured at 298.15K.